Coronary dominance and prognosis in patients with chronic total occlusion treated with percutaneous coronary intervention. Issue 4 (10th August 2017) - Gebhard, Cathérine; Gick, Michael; Ferenc, Miroslaw; Stähli, Barbara E.; Ademaj, Fadil; Mashayekhi, Kambis; Buettner, Heinz Joachim; Neumann, Franz‐Josef; Toma, Aurel
Abstract: Aim: The prognostic value of coronary artery dominance pattern in patients with chronic total occlusions (CTO) is unknown. The aim of this study was to assess the influence of coronary vessel dominance on short and long‐term outcomes in patients undergoing percutaneous coronary intervention (PCI) for CTO. Methods and results: Our study population consisted of 2002 consecutive patients (17% females, mean age 65.2 ± 10.7 years) who underwent PCI of at least one coronary CTO lesion at our center between 01/2005 and 12/2013. Based on the origin of the posterior descending coronary artery, coronary circulation was categorised into left, right, and balanced coronary dominance. Right coronary dominance (RD) was present in 88% ( n = 1759), left coronary dominance (LD) in 7% ( n = 136), and balanced coronary dominance (BD) in 5% ( n = 107) of the study population. After a median follow‐up duration of 2.6 years [interquartile range 1.1–3.1 years] all‐cause mortality was significantly higher in patients with LD as compared with RD and BD (log rank = 0.001). Accordingly, the presence of a LD system was identified as a significant predictor for all‐cause mortality (adjusted HR 1.7, 95% CI: 1.2‐2.6, P = .007) and major adverse cardiac events (MACE) (adjusted HR 1.4, 95% CI: 1.1‐1.8, P = 0.02). Conclusion: Our data suggest that LD is an independent predictor of increased all‐cause death and MACE in patients with CTO. Therefore, assessment of coronary vessel dominance by angiography may contribute to risk stratification in these patients.